Third party funding for arbitration in Malaysia - Leong, Chun Yen, 1991-, author 610010; Jamaludin Yaakob, supervisor 603234; Fakulti Alam Bina 8041 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2016